Interface mechanical damage mechanism in machining carbon fiber-reinforced plastic/Ti stacks based on a three-dimensional microscopic oblique cutting model. (1st January 2022) - Li, Changping; Zhao, Yongfeng; Qiu, Xinyi; Li, Shujian; Niu, Qiulin; Li, Pengnan; Ko, Tae Jo
Highlights: A three-dimensional microscopic finite element oblique cutting model of CFRP/Ti stacks was established. The material removal process and damage formation mechanism in the interface zone of CFRP/Ti stacks were investigated. The relationship between the subsurface damage, fiber orientation, and cutting sequence was explored. The simulated machined surface morphology of the CFRP/Ti stack is in good agreement with the experimental results. Abstract: When machining stacks of carbon fiber-reinforced plastic (CFRP) and Titanium (Ti) alloy, the damage to the interface zone is an important factor that affects the machining quality. In this study, a three-dimensional microscopic finite element oblique cutting model was established to investigate the material removal process and damage formation mechanism in the interface zone. The relationship between the subsurface damage, fiber orientation, and cutting sequence was explored. The process of fiber removal and damage formation can be clearly observed in a simulation. The fiber orientation and cutting sequence have significant effects on the formation of subsurface damage in the interface zone. The formation mechanism of interface damage is described in detail. An experiment was performed to verify the simulation results. The simulated machined surface morphology of the CFRP/Ti stacks is in good agreement with the experimental results, which verifies the usefulness of the established model.